2019
DOI: 10.1371/journal.pmed.1002961
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution mapping of tuberculosis transmission: Whole genome sequencing and phylogenetic modelling of a cohort from Valencia Region, Spain

Abstract: BackgroundWhole genome sequencing provides better delineation of transmission clusters in Mycobacterium tuberculosis than traditional methods. However, its ability to reveal individual transmission links within clusters is limited. Here, we used a 2-step approach based on Bayesian transmission reconstruction to (1) identify likely index and missing cases, (2) determine risk factors associated with transmitters, and (3) estimate when transmission happened.Methods and findingsWe developed our transmission recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 44 publications
4
84
3
1
Order By: Relevance
“…We found that 13.1% (14/107) of the pulmonary TB cases had genomic-clustered strains in Luodian county during a period less than one year. The cluster rate was lower than the results of other studies, including one conducted in Shenzhen (25.2% , 105/417) during ve years 17 , and another one from Spain (33.5%, 109/325) in a 3-year population-based study 23 . The cluster rate in current study likely be underestimated by following reasons.…”
Section: Discussioncontrasting
confidence: 67%
“…We found that 13.1% (14/107) of the pulmonary TB cases had genomic-clustered strains in Luodian county during a period less than one year. The cluster rate was lower than the results of other studies, including one conducted in Shenzhen (25.2% , 105/417) during ve years 17 , and another one from Spain (33.5%, 109/325) in a 3-year population-based study 23 . The cluster rate in current study likely be underestimated by following reasons.…”
Section: Discussioncontrasting
confidence: 67%
“…However, our finding reconfirmed that TB transmission was ongoing in the community. A comprehensive molecular characterization of withinhost M. tuberculosis diversity, as well as an attempt to temporally identify the primary source or index of transmission by comparing diagnosis times and the times of symptom onset (20), might be needed to fully capture TB transmission chains and accurately infer TB transmission (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…2). Because the in vivo mutation rate of Mtb is approximately 0.24 to 0.5 SNPs per genome per year (17,(19)(20)(21), this disparity suggested that the mutation rate in vivo might not be uniform. To test this, we simulated Mtb population growth in silico using a growth model with a constant mutation rate (Wright-Fisher model) (22).…”
Section: Mutation Rate Varies Between Bacilli Within a Single Individualmentioning
confidence: 99%